COMBINED OPTIMAL TAP SETTING AND REACTIVE POWER INJECTION FOR LOSS REDUCTION IN DISTRIBUTION SYSTEMS (2014)
This paper presents an optimization model for a combined scheme of optimal tap setting and reactive power injection in distribution systems. The proposed model provides the reactive power injection and tap setting scheme that would minimize losses, keeping voltage magnitudes within specified limits, at minimum cost. The formulation is done as an optimal reactive power flow and is solved using commercial available software. Several tests are performed on a 33-bus distribution test system. The results obtained showed that the combined use of tap setting and reactive power injection leads to higher loss reduction than the use of any of these actions separately.